The interference of anti-TSH autoantibody on clinical TSH detection - Tang, Mulin; Meng, Xue; Ni, Jiajia; Liu, Xue; Wang, Xinhui; Li, Yuchen; Chai, Yuwei; Kou, Chunjia; Zhang, Li; Zhang, Haiqing (Frontiers in Endocrinology, 2024)
Objective: It is well known that Macro-TSH may interfere with the detection of TSH. Anti-TSH autoantibody is the essential component of Macro-TSH. However, it is unclear about the epidemiological characteristics and clinical interference of anti TSH autoantibody. Methods: We used the radioimmunoprecipitation technique to detect anti-TSH autoantibody. Platforms with different detection mechanisms were applied to detect TSH in patients with anti-TSH autoantibody. PEG precipitation was used to determine the immunoassay interference. Results: The prevalence of anti-TSH autoantibody in patients who have mild SCH and have autoimmune thyroiditis but normal thyroid function is 4.78%. All 10 patients with anti-TSH antibodies have autoimmune diseases, 5 of them have significant-clinical test interference. Conclusions: The appearing of anti-TSH antibody is not associated with thyroid autoantibodies. The presence of anti-TSH autoantibody can interfere with the detection of TSH and affect clinical diagnosis and treatment.